Microbiological quality of raw drinking milk and unpasteurised dairy products: results from England 2013–2019. (2020) - McLauchlin, J.; Aird, H.; Elliott, A.; Forester, E.; Jørgensen, F.; Willis, C.
Abstract: The aim of this study was to review microbiology results from testing >2500 raw drinking milk and dairy products made with unpasteurised milk examined in England between 2013 and 2019. Samples were collected as part of incidents of contamination, investigation of infections or as part of routine monitoring and were tested using standard methods for a range of both pathogens and hygiene indicators. Results from testing samples of raw cow's milk or cheese made from unpasteurised milk for routine monitoring purposes were overall of better microbiological quality than those collected during incident or investigations of infections. Results from routine monitoring were satisfactory for 62% of milks, 82% of cream, 100% of ice-cream, 51% of butter, 63% of kefir and 79% of cheeses, with 5% of all samples being considered potentially hazardous. Analysis of data from cheese demonstrated a significant association between increasing levels of indicator Escherichia coli with elevated levels of coagulase positive staphylococci and decreased probability of isolation of Shiga toxin-producing E. coli . These data highlight the public health risk associated with these products and provide further justification for controls applied to raw drinking milk and dairy products made with unpasteurised milk.